1997
DOI: 10.1164/ajrccm.155.4.9105087
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-bound and soluble alpha IL-5 receptor mRNA in the bronchial mucosa of atopic and nonatopic asthmatics.

Abstract: Eosinophilic inflammation and interleukin-5 (IL-5) expression are characteristic features of the bronchial mucosa in asthma. We have investigated the differential expression of membrane and soluble isoforms of alpha IL-5 receptor (alpha IL-5Rm and alpha IL-5Rs) mRNA in asthmatics and in normal control subjects and examined the correlation between alpha IL-5Rm and alpha IL-5Rs expression and the FEV1 and airway hyperresponsiveness. Nineteen subjects with stable asthma (atopic = 9; intrinsic = 10) and 22 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 23 publications
5
43
0
1
Order By: Relevance
“…ϩ cord blood cells have been shown to produce mainly IL-5R mRNA coding for the soluble isoform of the ␣-chain (18) and Yasruel et al (52) have shown that the expression of sIL-5R␣ mRNA in bronchial biopsies of atopic and nonatopic asthmatics directly correlated with the patients' FEV 1 . As such, factors that induce production of the soluble isoform of the IL-5R may prove highly useful for abrogating eosinophil development as well as other IL-5-mediated events.…”
Section: Discussionmentioning
confidence: 99%
“…ϩ cord blood cells have been shown to produce mainly IL-5R mRNA coding for the soluble isoform of the ␣-chain (18) and Yasruel et al (52) have shown that the expression of sIL-5R␣ mRNA in bronchial biopsies of atopic and nonatopic asthmatics directly correlated with the patients' FEV 1 . As such, factors that induce production of the soluble isoform of the IL-5R may prove highly useful for abrogating eosinophil development as well as other IL-5-mediated events.…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of IL-5R ␣-chain in the bone marrow supports the concept that IL-5 is intricately involved in eosinophilopoiesis, and also one important effect of this cytokine is localized to immature eosinophils bearing IL-5Rs. In humans, it has been shown that mRNA specific for the ␣-chain of IL-5R can be found also in airway tissue (40,51), and it is possible that this mRNA expression leads to IL-5R expression on the cell surface. Certainly, it is likely that airway eosinophils do express small numbers of functionally active IL-5Rs, which, however, are impossible to stain by immunocytochemical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In a human clinical correlate, an important component of the allergic response is mediated by eosinophils whose production and activity are significantly stimulated by IL-5. In patients with allergic asthma, the level of mRNA encoding the membranebound IL-5 receptor in endobronchial biopsy samples increases with the severity of bronchial constriction [124]. As treated patients recover from an acute asthmatic episode, expression of soluble IL-5 receptor mRNA increases, suggesting that the soluble IL-5 receptor may counteract the effects of IL-5 in the lung and its increased expression may effect recovery from asthma.…”
Section: The Role Of Soluble Receptors In Normal Physiology and Pathomentioning
confidence: 99%